Analisis Ketidaksesuaian Upah Buruh Dengan Perbandingan Upah Minimum Regional - Ferdinand S, Josua; Ardiana, Oktavia Dwi; Azzahra, Dinda; Putri, Maria Sylvia; S, Satino (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Analysis of the Discrepancy in Labor Wages with Regional Minimum Wage Comparisons is an in-depth study of the wage gap between workers and the minimum wage standards applicable in a region. This article aims to identify the factors that cause this mismatch, its impact on workers' welfare and regional economic stability, as well as the efforts made by the government to overcome this problem through statutory regulations. Based on previous research and analysis of applicable regulations, this article illustrates that the minimum wages set by the government are not always followed by business actors, so that many workers still receive wages below the set standards. Factors that cause this include the company's drive to increase profits by reducing labor costs, intense competition in the market, lack of worker skills and productivity, and lack of supervision and law enforcement from the government. Therefore, this article highlights the important role of the government in monitoring and enforcing compliance with minimum wage standards, and emphasizes the need for joint efforts from all relevant parties to create a fairer and more comfortable working environment for workers.